Surface modification of polystyrene beads by UV/Ozone treatment - Ahmad Nor, Yusilawati; Mel, Maizirwan; Sopyan, Iis; Hamzah, Mohd. Salleh; Ng, K.H.; Wong, Chiow San (Trans Tech Publications, Switzerland, 2011)
It is known that polystyrene must be chemically modified to make its surface amenable to covalent cross-linking with protein. The aim of this study was to set up a UV/Ozone system and investigate the effects of UV/Ozone treatment on polystyrene surface. Microsize polystyrene beads with an average size of 150 μm in diameter were treated with and without distilled water at the same treatment time, ozone flow-rate and UV intensity. The treated beads were analyzed by ATRFTIR, SEM, EDX and hydrophilicity measurement. The results show that the hydrophilicity of the surface of polystyrene beads was increased after the UV/ozone treatment and the introduction of carbonyl, carboxyl and hydroxyl groups on the polystyrene beads surface was also confirmed. It was demonstrated that the UV/Ozone system was effective for treatment of polystyrene bead and the best result was obtained without distilled water